Robot-assisted pyeloplasty and laparoscopic pyeloplasty in children: A comparison of single-port-plus-one and multiport surgery - Jianglong Chen; Jianglong Chen; Huihuang Xu; Huihuang Xu; Shan Lin; Shan Lin; Shaohua He; Shaohua He; Kunbin Tang; Kunbin Tang; Zhixiang Xiao; Zhixiang Xiao; et al. (Frontiers Media S.A., 2022)
ObjectiveThis study aimed to compare the effects of various trocar placements in robot-assisted and laparoscopic pyeloplasty involving children diagnosed with obstruction of the ureteropelvic junction (OUPJ).MethodsWe retrospectively collected the data on 74 patients under 14 years of age who had been diagnosed with OUPJ; these patients underwent either robot-assisted or laparoscopic pyeloplasty in our hospital between January 2015 and November 2021. There were four groups, as follows: •Laparoscopic multiport pyeloplasty (LMPY),•Laparoscopic single-port pyeloplasty (LSPY),•Robotic-assisted multiport pyeloplasty (RMPY),•Robotic-assisted single-port-plus-one pyeloplasty (RSPY).Patients' characteristics as well as their perioperative and follow-up data were collected and evaluated.ResultsThere was no significant difference in the data regarding patients' characteristics. These data included the grade of hydronephrosis according to the Society of Fetal Urology (SFU grade), anterior and posterior diameter of the renal pelvis and ureter (APDRPU), and the differential degree of renal function (DRF) at following time points: preoperative, postoperative, and comparison of preoperative and postoperative. There was no difference among these groups. During surgery, the time of trocar placement, urethroplasty time, and total operative time in the robotic groups (RMPY and RSPY) were longer than those in the laparoscopic groups (LMPY and LSPY). However, the ratio of the urethroplasty time and full operative time (UT/WT) in the robotic groups (RMPY and RSPY) was lower than that in the laparoscopic groups (LMPY and LSPY) (P = 0.0075). Also, the volume of blood loss was lower in the robotic groups (RMPY and RSPY) than that in the laparoscopic groups (LMPY and LSPY), although there was no statistical difference (P = 0.11). There were, however, significant differences in hospitalization days (P < 0.0001) and parents' cosmetic satisfaction scores (P < 0.001). There were no differences in fasting time, the length of time that a ureteral catheter remained in place, or the number of postoperative complications.ConclusionOur study shows that both robotic multiple-port and single-port-plus-one approaches are comparable, with laparoscopic multiple-port and single-port approaches equally effective in resolving OUPJ in children. Robotic and single-port-plus-one approaches may be associated with some advantages in hospitalization time and cosmetic outcomes; therefore, these approaches may be useful in urologic surgery that requires precise suturing, especially in pediatric patients.